Antioxidant and Anti-inflammatory Activities of the Siamese Crocodile (Crocodylus Siamensis) Hemoglobin Hydrolysate Derived from Trypsin and Papain Hydrolysis - Jiraporn Lueangsakulthai (Science Faculty of Chiang Mai University, 2019)
Crocodylus siamensis hemoglobin hydrolysates (CHHs) were obtained by trypsin and papain digestion at different incubation times (2, 4, 6 and 8 h) at 37 °C and subjected to antioxidant and anti-infl ammatory activity assessment. DPPH scavenging activity of CHH derived from trypsin was similar to intact Hb. CHH derived from papain hydrolysis by 8-h hydrolysis (8h-CHHp) showed the highest DPPH scavenging activity at 56.86% antioxidant inhibition with IC50 value of 31 μg/ml. CHH derived from papain hydrolysis by 2-h hydrolysis (2h-CHHp) showed the highest reducing power activity at 0.99 mM Trolox equivalent and 4h-CHHt showed reducing activity at 0.16 mM Trolox equivalent (at concentration of 500 μg/ml). The linoleic peroxidation activity of CHH derived from papain hydrolysis by 6-h hydrolysis (6h-CHHp) and CHH derived from trypsin hydrolysis by 8-h hydrolysis (8h-CHHt) was increased in a dose-dependent manner with IC50 value of 5 μg/ml. The strongest anti-infl ammatory activity was found for 2h-CHHp, which displayed a high effi cacy in decreasing NO production of macrophage RAW 264.7 cells (46.86%) with no toxicity and signifi cantly reduced pro-infl ammatory cytokines interleukin-6 (IL-6) production to about 25.73 pg/ml. Taken collectively, the results of this work demonstrate that CHHs derived from papain hydrolysis possesses antioxidant and anti-infl ammatory activities, which provides support for the application against infl ammation and oxidative stress-related disorders.